2006
DOI: 10.1007/bf03175035
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition effects onto antimicrobial and antioxidant activities of propolis collected from different regions of Turkey

Abstract: Gunduz et al. 2005, Sonmez et al. 2005, S , ahinler and Kaftanoglu, 2005Silici and Kutluca, 2005;Uzel et al., 2005). In this study, antimicrobial and antioxidant activities of propolis samples from different regions of Turkey were examined and these effects were investigated depending to the chemical composition of ethanol extract of propolis samples. MATERIALS AND METHODS Propolis samples and preparation of alcohol extracts.Eight samples of propolis were collected from Denizli (P1, P5), Denizli-Sarayköy (P2A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…Pterocarpan medicarpin in Brazilian red propolis was a phytoalexin which demonstrated strong antifungal activity against Candida albicans (Fernandes, Lopes, Colombari, Monteiro, & Vieira, 2006). While in Turkey propolis the main antimicrobial compound was chrysin (Mercan et al, 2006) and in Bulgarian propolis galangin was the most active flavonoid against Campylobacter jejuni (Campana et al, 2009). Therefore, the antibacterial compounds in propolis could be qualitatively and quantitatively different with the variation dependent upon the region where it was collected.…”
Section: Discussionmentioning
confidence: 96%
“…Pterocarpan medicarpin in Brazilian red propolis was a phytoalexin which demonstrated strong antifungal activity against Candida albicans (Fernandes, Lopes, Colombari, Monteiro, & Vieira, 2006). While in Turkey propolis the main antimicrobial compound was chrysin (Mercan et al, 2006) and in Bulgarian propolis galangin was the most active flavonoid against Campylobacter jejuni (Campana et al, 2009). Therefore, the antibacterial compounds in propolis could be qualitatively and quantitatively different with the variation dependent upon the region where it was collected.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, in 57 of 64 samples, ethyl oleate was determined at considerably high ratios. Similarly, this compound was determined in other propolis samples of Turkey [3,76,77]. Determination of ethyl oleate in different ratios in many propolis samples (57 samples) suggests that this compound may be a marker compound for the Hakkari region or even Turkey propolis.…”
Section: Resultsmentioning
confidence: 83%
“…In other countries of Southern European Coast, such as Turkey, chemical composition of propolis has widely investigated by several authors. Quercetin (26), rutin (48), chrysin (2), pinocembrin (3), pinostrobin chalcone (49) and pinobanksin (1) and its derivatives were the most repeated flavonoids found in various simples of propolis from Turkey using different method of analysis such as gas chromatography-mass spectrometry (GC/MS), high-performance liquid chromatography (HPLC) and ultrahigh-performance liquid chromatography with a linear ion trap-high resolution Orbitrap mass spectrometry system (UHPLC-LTQ/orbitrap/MS/MS), [73,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] while Erdogan et al [96] have reported the presence of other flavonoids such as gallocatechin (50), epigallocatechin (51) and myricetin (52) in Anatolian propolis submitted to a pressurized liquid extraction. Other authors did not report the presence of flavonoids in Turkish propolis originating from Hatay, Ankara-Kazan and Mugla-Marmaris, [97 -100] at the same time they declared that terpenes such as αand β-eudesmol, isopimaric acid (42), dehydroabietic acid (53) and abietic acid (54) ( Figure 4) were included in the bioactive compounds of tested propolis samples.…”
Section: Southern European Coastmentioning
confidence: 99%
“…[8,35,76,80,85,96,99,106,135,149 -155] Furthermore this biological property of Turkish propolis was confirmed through other assay such as heat-induced oxidation of an aqueous emulsion system of β-carotene and linoleic acid assay where the total antioxidant activity increased with the increasing amount of extracts added to linoleic acid emulsion. [80] Also, a screening method for antioxidant activity used reversed Phase HPTLC-DPPH free radical assay. [89] In general, the antioxidant capacity of different Turkish propolis extracts was assessed to be positively correlated with their total polyphenol content.…”
Section: Southern European Coastmentioning
confidence: 99%